Proterodiplostome Parasites (Digenea, Proterodiplostomidae) of the Caiman, Caiman crocodilus yacare (Reptilia, Crocodylia) in the Pantanal mato-Grossense, Brazil, with the description of two new species - João B. Catto; J. F. R. Amato (Memorias do Instituto Oswaldo Cruz, 1994)
Two new species are described from the caiman. Caiman crocodilus yacare. Proterodiplostomum breve n. sp. differs from all other species in the genus by the following chacacteristics: (1) the paraprostate gland is shorter and club-shaped; (2) the genital cone is, in average, eight times longer than that of P. medusae; (3) the genital atrium is larger and without pseudosuckers; (4) the oral sucker and pharynx are longer; and (5) there are larger numbers of papillae surrounding the tribocytic organ (40) against 20 in P. longum, 16 in p. tumidilum, 8 in P. ophidum, and 16-18 in P. medusae. Proterodiplostomum globulare n. sp. differs from all the other species in the fenus by the following characteristics: (1) from P. tumidilum, P. lomgum, P. medusae, and P. breve n. sp. for the absense of pseudosuckers or muscular bunches in the inferior wall of the genital atrium; (2) the shape of the paraprostate gland, which is globular and not cylindrical as in P. longum, P. tumidilum, P. medusae, and P. ophidum; (3) the size of the tribocytic organ 201-407 long, 183-495 wide, while is 138-270 long, 102-292 wide in P. medusae, and 138-270 long, 255 wide in P. ophidum; (4) the number of papillae in the tribocytic organ (18-20) in P. globulare and 16-18 in P. medusae, and 8 in P. ophidum. Specimens belonging to six other species of proterodiplostomes are recorded for the first time infecting the caiman, C. c. yacare in the Pantanal Mato-grossense, Brazil, namely: Proterodiplostomum medusae, P. tumidilum, Cystodiplostomum hollyi, Prolecithodiplostomum constrictum, Paradiplostomum abbreviatum, and Herpetodiplostomum caimancola.